METODE FIEL-TRIP DALAM MENUMBUHKAN KEPEDULIAN SISWA TERHADAP PENINGGALAN SEJARAH BUKTI-BUKTI KEHIDUPAN PENGARUH HINDHU BUDHA YANG MASIH ADA PADA SAAT INI - Tatik Widyawati; Puspita Pebri Setiani (UNIVERSITAS INSAN BUDI UTOMO, 2019)
The purpose of this research was to know effect from field-trip method to cultivate a caring of Hindhu-Budhist’s historical heritage in grade 10th MA AL HISI. The research method was used quasi experimental with nonequivalent control group desaign. Data were taken from 30 respondents of grade 10th of MA AL HISI. Data collection techniques use questionnaire, documents and observation. The hypotesis test use a paired sample t-test with a significance of 0.05. Field-trip implementation in grade 10th was good category, it came from observation that have value of 87. The caring in grade 10th MAAL HISI has increased seen from the result of average value from 79,2 to 93,1. The influence of the field-trip method on student care is high,it seen from the significance value of t-test 0,000 <0.05. So there is an influence between the field-trip method and the level of concern for students of class X MA AL HISI.